IBM DS8900F product guide - Kimmel, Peter (IBM Redbooks, 2020)
Built on over 50 years of Enterprise storage expertise, the IBM® DS8000® series is the flagship of disk storage systems within the IBM System Storage"!portfolio. As of September 2019, the DS8900F is the latest addition and offers two new classes: DS8910F: Flexibility Class all-flash DS8950F: Agility Class all-flash The agility class is efficiently designed to consolidate all your mission-critical workloads for IBM Z®, IBM LinuxONE, IBM Power Systems, and distributed environments under a single all-flash storage solution. This IBM Redbooks® Product Guide gives an overview of the features and functions that are available with the IBM DS8900F models running microcode Release 9.0 (Bundle 89.0 / Licensed Machine Code 7.9.0.xxx)
Online resource; title from resource description page (Safari, viewed June 5, 2020)
Keywords: Cloud computing; Infonuagique